Constituent-tunable ternary CoM2xSe2(1−x) (M = Te, S) sandwich-like graphitized carbon-based composites as highly efficient electrocatalysts for water splitting. Issue 13 (14th March 2019) - Wang, Yu; Liu, Li; Wang, Yanwei; Fang, Ling; Wan, Fu; Zhang, Huijuan
Abstract : Herein, we synthesized two groups of component-controllable sandwich-like CoTe2 x Se2(1− x ) and CoS2 y Se2(1− y ) graphitized carbon-based catalysts for the first time. Abstract : Herein, we fabricated two groups of component-tunable sandwich-like CoTe2 x Se2(1− x ) and CoS2 y Se2(1− y ) graphitized carbon-based composites. Due to the synergistic effect between the sandwich-like structures and anion-doping, CoTe2 x Se2(1− x ) and CoS2 y Se2(1− y ) demonstrated attractive catalytic performance towards the oxygen evolution reaction (OER) and hydrogen evolution reaction (HER), respectively. After optimizing the composition, we found that sandwich-like Co(Te0.33 Se0.67 )2 possesses optimal OER properties, with a low Tafel slope (44 mV dec −1 ), a small η 10 (272 mV) and eminent stability for 50 h; meanwhile, the Co(S0.72 Se0.28 )2 catalyst presents attractive HER performance, featuring a minimum Tafel slope (80 mV dec −1 ) and a low η 10 (106 mV) in alkaline media. Additionally, density functional theory (DFT) calculations confirmed that Δ G H* of the Co(S0.72 Se0.28 )2 catalyst (0.182 eV) is closest to zero. Therefore, an alkaline electrolyzer was fabricated using Co(Te0.33 Se0.67 )2 as the anode and Co(S0.72 Se0.28 )2 as the cathode; it manifested striking catalytic activity and favorable stability for overall water splitting. This is the first time that the effects of different dopants (Te and S atoms) and doping contents on the electrocatalytic performance of CoSe2 were explored towards overall water splitting. Also, this research provides a new pathway for the fabrication of ternary dianion transition metal dichalcogenides as admirable electrocatalysts for water splitting.